2006
DOI: 10.1148/rg.261055045
|View full text |Cite|
|
Sign up to set email alerts
|

T1 Signal Hyperintensity in the Sellar Region: Spectrum of Findings

Abstract: T1 signal hyperintensity is a common finding at magnetic resonance imaging of the sellar region. However, this signal intensity pattern has different sources, and its significance depends on the clinical context. Normal variations in sellar T1 signal hyperintensity are related to vasopressin storage in the neurohypophysis, the presence of bone marrow in normal and variant anatomic structures, hyperactive hormone secretion in the anterior pituitary lobe (eg, in newborns and pregnant or lactating women), and flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 33 publications
6
112
0
8
Order By: Relevance
“…In the MR images, acute and subacute hemorrhage characteristically exhibited T1 hyperintensity on pre-contrast imaging with minimal or no enhancement on post-contrast imaging, consistent with previous descriptions of intratumoral hemorrhage [21][22]. The tumor was distinguished from normal pituitary by virtue of its morphology and hypoenhancement on post-contrast T1-weighted images.…”
Section: Software-calculated Volumetric Measurementsupporting
confidence: 86%
“…In the MR images, acute and subacute hemorrhage characteristically exhibited T1 hyperintensity on pre-contrast imaging with minimal or no enhancement on post-contrast imaging, consistent with previous descriptions of intratumoral hemorrhage [21][22]. The tumor was distinguished from normal pituitary by virtue of its morphology and hypoenhancement on post-contrast T1-weighted images.…”
Section: Software-calculated Volumetric Measurementsupporting
confidence: 86%
“…Repeated bleeding may occur on the basis of ischemic necrosis or hemorrhagic necrosis (11)(12)(13). Various previous studies have suggested that fluid-fluid level within a fluid cavity is induced by the sedimentation of blood products at the subacute or chronic stage, as well as the separation of unclotted blood as opposed to serous (interstitial) fluid (6,(10)(11)(12)14,15). These studies indicate that fluid-fluid levels are typically presented as high/low signal patterns on axial (or sagittal) T2-weighted images, or partially on T1-weighted images as high/slightly high (or isointense) features.…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, RCC is typically exhibited as an intrasellar cystic lesion with suprasellar extension that is ovoid or kidney shaped and well demarcated, and exhibits no calcification, a lack of or a thin cyst wall enhancement, orintracystic nodules (2). Craniopharyngiomas are typically presented as superiorly lobulated shaped sellar-suprasellar heterogeneous lesions, with mixed solid and cystic characteristics, calcification, reticular enhancement of the solid portion, and third ventricle compression by superior tumor extension (8,15,23). In various previous studies, intracystic nodules have been regarded to have diagnostic value for RCC, which typically displays distinctive characteristics, including T1-weighted hyperintensity, T2-weighted hypointensity, and no gadolinium enhancement (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After gadolinium, a peripheral enhancement is represented by a thin peripheral rim. In the chronic phase, there is signal increase in both T 1 and T 2-weighted images (39,40).…”
Section: Imaging Follow-upmentioning
confidence: 99%